The Sources of Drinkable Water Used and Its Related Diseases among Barangay Capual Residents Omar, Sulu - Warid-Sahial, Ayesha Pesy; Hayudini, Magna Anissa A.; Gadong, Raima J.; Ujad, Rheada J.; Warid, Ledina Pesy; Hussin, Brenda A.; Kahalan, Ananghulma J.; Abdulpatta, Jardine; Alam, Hasanul Basariy B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The goal of this study is to determine the sources of drinking water and identify ailments among the respondents that are related to water consumption. The study was undertaken to ascertain the sources of drinking water used and its impact on health on Capual Island. The research will also determine whether the respondents' water-related illnesses are significantly impacted by their sources of drinking water. Residents of Capual Island will gain knowledge about local sources of drinking water and illnesses associated with water from the study. Male and female respondents from 287 households were polled. Regarding the data analysis and interpretation, a statistician was consulted. Frequency tables were used to present the data. For the study, the researchers utilized a descriptive-predictive research methodology. The entire population of Barangay Capual had been used by the researchers. The Rural Health Unit-Omar can help communities improve their drinking water by educating them on proper cleaning of their sources of drinking water, installing covers on their deep wells, making sure there are no animals in their water sources, and sanitizing their drinking water. Typhoid fever and diarrhea were the most common water-related diseases among respondents, topping the survey with 84.7% and 85.0%, respectively. Students pursuing a Bachelor of Science in Nursing degree should provide lectures on waterborne illnesses and inform residents of additional methods for sanitizing their drinking water. It is important to inform the people of Barangay Capual that their homes should have backup water sources. Additionally, according to the experts, filtering and boiling the drinking water before use is important and will lower the risk of contracting waterborne illnesses and their fatal consequences. Future researchers may use it as a backbone for further study by taking on other variables that were not tested in this study.